The Cabrillo Port: Get the Facts on BHP Billiton's Liquefied Natural Gas (LNG) Proposal for the Oxnard/Malibu Coast (California Coastal Protection Network)
BHP Billiton, the world's largest mining company, proposes to moor a massive three football field-long, 14 story-high, floating LNG storage and processing terminal, the Cabrillo Port, approximately 14 miles offshore the Ventura and LA County line near Leo Carrillo State Beach and the Malibu City limit.